Bloodstream infections with emphasis on Methicillin-resistant Staphylococcus aureus at the University of Gondar Comprehensive Specialized and Referral Hospital, Northwest Ethiopia - Minichil Worku; Solomon Belay; Tigist Molla; Azanaw Amare; Mitkie Tigabie; Wesam Taher Almagharbeh; Muluneh Assefa (BMC Infectious Diseases)
Abstract Background Staphylococcus aureus is the most common cause of bloodstream infections worldwide. Methicillin-resistant S. aureus is becoming more prevalent in bacteremia and septicemia cases. Thus, this study determined Staphylococcal bacteremia, Methicillin-resistant S. aureus infections, and antimicrobial susceptibility patterns of the isolates in Northwest Ethiopia. Methods and materials This retrospective cross-sectional study was conducted on all age bloodstream suspected patients at the University of Gondar Comprehensive Specialized and Referral Hospital from January 1th 2022 to June 30th, 2022. Data were collected using a designed data extraction tool. Blood samples were collected and inoculated to a sterile Tryptic Soya Broth. Bottles with bacterial growth were subcultured to blood agar, chocolate agar, MacConkey agar, and mannitol salt agar plates. Antimicrobial susceptibility testing was performed using the Kirby Bauer disc diffusion technique. The data were entered using Epi-info version 7 and exported to SPSS version 20 for analysis. Results Among 1200 patients included in this study, 719 (59.9%) were males. The prevalence of S. aureus and Methicillin-resistant S. aureus was 26.2% (111/424) and 68.5% (76/111), respectively. The blood culture growth rate was 35.3% (424/1200). Among the isolated organisms, Gram-positive cocci account for 217 (51.2%) and Gram-negative bacilli were 173 (41.0%). Among S. aureus isolates, 63.7% were sensitive to gentamicin and 91.9% were resistant to penicillin. A high prevalence of bacteremia was found in males (60.1%) and ward locations at the neonatal intensive care unit (57.1%). Specifically, Methicillin-resistant S. aureus was highly prevalent in males, followed by pediatric age groups, and neonatal intensive care unit, which were 59.2%, 56.6%, and 44.7%, respectively. Conclusion In this study, the prevalence of Methicillin-resistant S. aureus bacteremia was high, indicating its spread in hospital settings such as intensive care units. This requires routine detection, molecular characterization of mecA gene, and improved infection prevention at the healthcare facility.